Early childhood educators' experiences and perceptions of professionalism and professionalisation in the Asian context. Issue 1 (1st January 2017) - Monk, Hilary; Phillipson, Sivanes
ABSTRACT: Increasingly early childhood educators are referred to as "professionals, " but how do they view themselves in terms of professionalism? What does it mean to be an early childhood professional? This study explored the views of 78 Asian early childhood educators who were upgrading their qualifications to degree level. In groups of five to eight, participants visually created and explained metaphors of professionalism as a class activity. The visual metaphors were analysed using Gleeson's polytextual thematic analysis with Rogoff's personal, interpersonal and institutional planes as the theoretical framework. Findings revealed that the educators' perspectives of professionalism and professionalisation related to their work–life roles, their cultural understandings and relationships, and how they believed they were viewed by others in relation to the status of early childhood education. This study provides an insight into perceptions and challenges related to the developing professionalism and professionalisation of early childhood educators in Asian contexts.